The Addition of Peripheral Blood Inflammatory Indexes to Nomogram Improves the Predictive Accuracy of Survival in Limited-Stage Small Cell Lung Cancer Patients - Qi, Jing; Zhang, Jiaqi; Ge, Xingping; Wang, Xin; Xu, Liming; Liu, Ningbo; Zhao, Lujun; Wang, Ping (Frontiers in Oncology, 2021)
Backgrounds: Accumulated evidence for systemic inflammation response in several solid tumors prompts a possibility of prediction of patients’ prognosis in a more accessible and valuable manner. However, the prognostic value of peripheral blood inflammatory markers in limited stage small cell lung cancer (LS-SCLC) remains unclear. Therefore, we investigated the prognostic values of pre-treatment inflammatory indexes in LS-SCLC patients. Methods: We retrospectively identified 334 patients with LS-SCLC and collected their pre-treatment levels of neutrophil, platelet, lymphocyte, leukocyte, hemoglobin and albumin, then neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic inflammation index (SII) were calculated. Patients were dichotomized as low or high group based on their corresponding cutoff values, respectively. Univariate and multivariate analyses were conducted with a COX proportional hazard model.The least absolute shrinkage and selection operator (LASSO) COX regression analyses was performed to construct the inflammation-related prognostic scoring system named Risk for OS. Nomograms were established to provide prognostic information, allowing for more individualized prediction of survival. Results: Higher platelet, lymphocyte and albumin were indicators of favorable OS, whereas higher NLR and SII were accompanied by inferior OS. The prognosis of patients with high-Risk was significantly worse than that with low-Risk in both the training group and the validation group (both P < 0.001). A comparable AUC values between training group and validation group were observed, yielding to 1-, 3-, 5-year OS rates of 67.3% vs. 69.2%, 66.8% vs. 69.5% and 66.7% vs. 71.4%, respectively. Multivariate analyses revealed that Risk (HR = 0.551, P < 0.001) was an independent negative prognostic indicator for OS, which was further verified in the validation set. The addition of Risk to nomogram (C-index = 0.643) harbored improved predictive accuracy for OS when compared with that of clinical factors alone (C-index = 0.606), the AUC values of 1-, 3- and 5-year OS rates were 71.7% vs. 66.4%, 73.5% vs. 66.6% and 71.9% vs. 65.6%, respectively. Conclusions: Peripheral blood inflammatory indexes may be a non-invasive serum biomarker for poor prognosis in LS-SCLC. The addition of Risk to nomogram model could serve as a more powerful, economical and practical method to predict survival for patients with LS-SCLC.